Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2025)
This edition of NIU Journal of Humanities touches on Youth Advocacy and Pedagogical Instructions, Impact of Orphanage-Based Interventions, Human Resource Management and Artistic Enterprise, Symbology, Identity, and Show as well as Business Paradigm in Contemporary Painting Space. One of the papers, in this issue, reveals that pedagogical instructions enhanced climate sustainability by equipping youth with appropriate knowledge, skills, and platforms to engage in climate action initiatives. Youth advocacy conclusively, is expected to promote policy changes, community engagement, and sustainable practices while mitigating the impact of climate change. It is therefore, suggested that the holistic and inclusive approach to climate education should foster a generation of climate-conscious and empowered youth who can contribute to a more sustainable future for all. Another paper also reveals that access to educational resources, teacher quality and availability of school facilities and infrastructures determines Quality Education needed for Economic Growth in Nigeria. It recommends that Government should allocate more funds for public education in order to be accessible to all. This issue of NIU Journal of Humanities features many empirical and theoretical based articles which can be of great benefit to every reader.